Perancangan Sistem Informasi Prediksi Curah Hujan Pada Kabupaten Jombang Menggunakan Metode Fuzzy Time Series - Suhartanto, Martin; Dwi Nuryana, I Kadek; Heru Mujianto, Ahmad (Inovate, 2021)
Weather and climate information is very important for some people to support life. In agriculture, for example, climate change has a major effect on changing planting patterns. Fuzzy Time Series (FTS), Rainfall prediction is used to understand the intensity of future rainfall that serves as a reference in making the right decisions and preparing to address future problems. In this study using the Fuzzy Time Series (FTS), this method can be used to solve forecasting problems with linguistic historical data and real numbers by converting the real number data into linguistic variables. The results of this study are a website-based system that can predict rainfall in the coming year by using previous rainfall history data as a reference for prediction calculations. from the calculation done by the system in predicting rainfall by using the Fuzzy Time Series method as an example in this silver sub-district produces an average mape value of 0.90 which means it has excellent performance because it produces an average mape forecasting error value of less than 10. Key words: Prediction, Rainy, FTS, website